Fatores econômicos, qualidade de vida e fragilidade de pessoas idosas residentes na comunidade - Silva, Elaine Santos da (Universidade Federal de São Carlos, 2022)
Introduction: aging is not synonymous with disability and dependence, but the accumulation of age-related conditions and conditions can cause greater vulnerability, so it is relevant to better understand the adversities that influence quality of life, such as the frailty syndrome and the economic factors. Objective: to verify the relationships between economic factors, quality of life and frailty of elderly people residing in the community and registered at the Family Health Strategy Unit, in the periods of 2015 and 2018. Method: this is an exploratory prospective longitudinal study, of a quantitative nature, developed in the city of São Carlos, of 223 elderly people. With data collection through interviews carried out in the participants' homes. The following instruments were used: a semi-structured questionnaire to assess sociodemographic and economic data; Short Form 6 Dimension, to assess quality of life, and the Edmonton Frailty Scale, to classify frailty. Continuous data are presented as mean ± standard deviation or median, according to the Shapiro-Wilk normality test, categorical variables are presented as absolute frequency (relative frequency), and comparisons between groups were performed using the test of Wilcoxon-Mann-Whitney for continuous variables and Pearson's chi-square test with Yates continuity correction for categorical variables. Results: most individuals were female (57.4%), with a median age of 68 years, married (63.2%) and most do not live alone (85.2%). Regarding economic factors, the majority did not have a job (70.9%) and received some type of social security benefit – retirement or pension (81.6%) per capita income was R$ 724.00. The mean quality of life score was 0.75 ± 0.15. At baseline, there were 59 (26.5%) frail while 73 (40.8%) were vulnerable and 91 (32.7%) were non-frail, and the mean frailty score as a linear function of time and variables showed a statistically significant association with age (Coef.β: 0.046 95% CI: 0.021 – 0.071; p < 0.001), male gender (Coef.β: - 0.915 95% CI: 1.275 – -0.555; p < 0.001) and quality of life (Coef.β: - 6,348 95% CI: -7,581 - -5,114; p < 0.001). Conclusion: in the initial assessment, most participants were vulnerable, and during follow-up, non-frail individuals became frail without being classified as vulnerable, showing that the progression of frailty exists and is not linear. It was also noted that there is a relationship between frailty and the quality of life of the elderly, corroborating the literature and affirming the importance of social and health care to change this situation in order to prevent the progression of frailty in elderly people. and the decrease in the negative perception of quality of life.
Economic factors, quality of life and frailty of community-dwelling elderly people
Factores económicos, calidad de vida y fragilidad de ancianos residentes en la comunidad
Keywords: Envelhecimento; Fatores econômicos; Fragilidade; Pessoa Idosa; Qualidade de vida; Aging; Economic factors; Fragility; Elderly; Quality of life; CIENCIAS DA SAUDE::ENFERMAGEM